2021
DOI: 10.1002/ca.23793
|View full text |Cite
|
Sign up to set email alerts
|

The atrioventricular conduction axis and the aortic root—Inferences for transcatheter replacement of the aortic valve

Abstract: Conduction problems still occur following transcatheter aortic valvar replacement.With this in mind, we have assessed the relationship of the conduction axis to the aortic root. We used serial histological sections, made perpendicular to the base of the triangle of Koch in nine hearts, and perpendicular to the aortic root in 11 hearts.We first defined the extent of the fibrous tissues forming the boundaries of an infero-septal recess of the subaortic outflow tract, found in all datasets but one.When the recess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 32 publications
9
25
0
Order By: Relevance
“…Taken overall, therefore, and in keeping with our previous investigation using a 2D approach (Macías et al, 2022), significant variability was found in the location of the conduction axis relative to the aortic root (Tables S2 and S3). When assessing these findings, we considered only the rightward extent of fibrous continuity between the leaflets of the aortic and mitral valves as the right fibrous trigone.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Taken overall, therefore, and in keeping with our previous investigation using a 2D approach (Macías et al, 2022), significant variability was found in the location of the conduction axis relative to the aortic root (Tables S2 and S3). When assessing these findings, we considered only the rightward extent of fibrous continuity between the leaflets of the aortic and mitral valves as the right fibrous trigone.…”
Section: Resultssupporting
confidence: 87%
“…The findings, achieved using 3D reconstructions of the root, expand our previous findings obtained using more traditional histological techniques (Macías et al, 2022). These showed that, in the variations placing the conduction axis at greatest risk, the component of the axis closest to the aortic root is the superior fascicle of the left bundle branch.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…On occasion, the relationship can be very close (figure 7). 39 This proximity is likely to determine the risk of conduction damage subsequent to transcatheter replacement of the aortic valve 40. The third septal division unites the fascicles that run towards the papillary muscles.…”
Section: The Criteria For Recognition Of the Components Of The Conduc...mentioning
confidence: 99%